Comparison of the teacher identity perception of novice science teachers through a mixed-methods approach. - Luque-Jiménez, Jorge; García-Ruiz, Cristina (ESERA, 2023)
Despite research on teacher identity contributes to understanding teacher learning and development, studies carried out with novice teachers (with less of five years of professional experience) are still rare due to the difficulties of finding participants at this stage. Consequently, this study aims to know how novice science teachers perceive their teacher identity through a mixed-methods approach. Hence, we have compared the data collected from an open-question survey and a Likert-type questionnaire adapted from literature to seek for matching results, evidencing in this way the consistency of these novice teachers’ perception about their teacher identity. Results show how pre-service teaching training provided novice teachers with a notion of their teacher identity, establishing the differences and similarities with other educational stages, and highlighting the factors, such as the Master´s Degree, placement period or teacher motivation, that have an influence in constructing their teaching identity.
Keywords: Profesores - Formación profesional; Profesores de ciencias - Formación profesional; Professional development; Teacher identity; Novice teachers